PERPETUAL PEACE DI KAWASAN INDO-PASIFIK: Penerapan Collective Security, Arms Control, dan Confidence Building Measures di Kawasan - Ryantori; Haryanto, Agus; Yovana, Kesi (Universitas Cenderawasih, 2025)
The ongoing strategic competition between China and the United States raises concerns about potential conflicts in the Indo-Pacific. However, achieving long-term stability in the region through cooperative security frameworks is essential. The realization of a peaceful region that fosters mutually beneficial cooperation is a non-negotiable goal in positive international relations. This article explores the possibility of achieving this in the Indo-Pacific from an International Relations perspective, particularly through the concepts of collective security, arms control, and confidence-building measures (CBMs). It argues that implementing these three concepts will lead to sustainable peace (perpetual peace), ultimately making the region a platform for mutually beneficial cooperation. A qualitative method is employed in this study, with data emanating from relevant literature and authoritative sources. While challenges such as military competition and geopolitical tensions persist, shared commitment to multilateral mechanisms can mitigate risks. The key factor in achieving this goal is a shared commitment to maintaining the process. KEYWORDS Collective Security; Confidence-Building Measures; Indo-Pacific; Regional Peace